2022
DOI: 10.1101/2022.04.19.22274056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Primary and Booster COVID-19 mRNA Vaccination against Omicron Variant SARS-CoV-2 Infection in People with a Prior SARS-CoV-2 Infection

Abstract: ImportanceThe benefit of primary and booster vaccination in people who experienced prior SARS-CoV-2 infection remains unclear.ObjectiveTo estimate the effectiveness of a primary (two-dose) and booster (third dose) vaccination against Omicron infection among previously infection people.DesignTest-negative case-control study.SettingYale New Haven Health System facilities serving southern Connecticut communities.ParticipantsVaccine eligible people who received SARS-CoV-2 RT-PCR testing between November 1, 2021, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
6
16
0
Order By: Relevance
“…Compared to prior studies, 8,2628 our estimates for protection against reinfection were substantially lower than those analyzing infections during pre-Omicron outbreaks; furthermore, we found significant differences in protection conveyed by prior infections before and during the emergence of the Delta variant. Consistent with other studies 11,14 , we found the highest levels of protection among those who had three doses of vaccination and prior infections. Among those with prior infection, the incremental protection afforded by vaccination was substantial, especially vaccination with three doses, which raised protection against Omicron infection to levels similar to those reported in pre-Omicron studies of vaccination with the primary series.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Compared to prior studies, 8,2628 our estimates for protection against reinfection were substantially lower than those analyzing infections during pre-Omicron outbreaks; furthermore, we found significant differences in protection conveyed by prior infections before and during the emergence of the Delta variant. Consistent with other studies 11,14 , we found the highest levels of protection among those who had three doses of vaccination and prior infections. Among those with prior infection, the incremental protection afforded by vaccination was substantial, especially vaccination with three doses, which raised protection against Omicron infection to levels similar to those reported in pre-Omicron studies of vaccination with the primary series.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to prior studies, 8,26-28 our estimates for protection against reinfection were substantially lower than those analyzing infections during pre-Omicron outbreaks; furthermore, we found significant differences in protection conveyed by prior infections before and during the emergence of the Delta variant. Consistent with other studies 11,14 , we found the highest levels of protection among those who had three doses of vaccination and prior infections.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…19 Studies examining protection against Omicron reinfection (BA.1 or any sublineage) have reported that prior pre-Omicron on infection was associated with moderate effectiveness (25% to 47%), but stronger against severe outcome (>80%), and improved with vaccination. 12,[18][19][20][21][22] As reported in our study, a third dose among previously infected individuals was associated to a transient increase in protection both against Omicron BA.1 and BA.2 subvariants. 12,19,20 Evidence about cross-protection between different Omicron sublineages is scarce.…”
Section: Discussionsupporting
confidence: 78%